Thermodynamic behaviour of solid–liquid grain boundary grooves. Issue 14 (17th July 2020) - Glicksman, Martin E.; Ankit, Kumar
ABSTRACT: Grain boundary grooves (GBGs) are local features that develop along polycrystalline solid–liquid interfaces. Interest in GBGs lies in their ability to form interface defects during crystallization that promote, in fact, dominate, morphological instability and affect microstructure formation in cast alloys. Recently, we reported on unobserved subtle aspects of the thermodynamic behaviour of GBG microstructures by combining sharp-interface field theory with diffuse-interface phase-field simulations. A surprising feature revealed about steady-state GBGs is that despite their stationarity they nonetheless support persistent capillary-mediated energy fluxes with divergences that continuously cool their interfaces and increase local curvatures. We now analyse the energetic behaviour of GBGs as 'open' thermodynamic systems, and report further details of their formation free energy that show how geometric constraints and capillary-mediated thermodynamic fields self-interact and influence the steady-state shapes of GBGs.